Measurement of the WZ production cross section in pp collisions at root s=7 and 8 TeV and search for anomalous triple gauge couplings at root s=8 TeV - KAYA, MİTHAT (SPRINGER, 2017)
The WZ production cross section is measured by the CMS experiment at the CERN LHC in proton proton collision data samples corresponding to integrated luminosities of 4.9 fb(-1) collected at root s = 7 TeV, and 19.6fb(-1) at root s = 8 TeV. The measurements are performed using the fully-leptonic WZ decay modes with electrons and muons in the final state. The measured cross sections for 71 < m(Z) < 111 GeV are sigma (pp -> WZ; root s = 7 TeV) = 20.14 +/- 1.32 (stat)+/- 0.38 (theo)+/- 1.06 (exp)+/- 0.44 (lumi) pb and sigma (pp -> WZ; root s = 8 TeV) = 24.09 +/- 0.87 (stat) 0.80 (theo) +/- 1.40 (exp) +/- 0.63 (lumi) pb. Differential cross sections with respect to the Z boson p(T), the leading jet p(T), and the number of jets are obtained using the root s = 8 TeV data. The results are consistent with standard model predictions and constraints on anomalous triple gauge couplings are obtained.
Keywords: TRILINEAR COUPLINGS